Teachers' professional dispositions and orientation towards tablet technology: towards a more nuanced understanding of teachers' adoption of technology in South African private secondary schools - Sackstein, Suzanne Lee (My University, 2014)
Rapid improvements in technology have resulted in increasing calls to integrate educational technology into classrooms. Much of the contemporary educational technology literature premised on constructivist pedagogic practices, have offered promissories of radical change to traditional pedagogic practices and formal education due to the use of educational technology. Past research has shown that teachers do not automatically choose to adopt technology in the classroom nor radically change their pedagogic practice, simply due to the presence of technology. Recent technological innovations such as mobile technologies, and more specifically tablets, are once more being advocated as a powerful means for radically transforming teachers’ teaching practices and enhancing learning in schools. Calls to incorporate tablet technology into the classroom are being driven by the groundswell of popular opinion demanding its inclusion, as well as contemporary research advocating constructivist pedagogic practices. Educational research thus far has explored classroom practices where technology has been adopted and has tended to focus on the resulting changes in teaching and learning. Research aimed at explicitly understanding teachers’ orientations to the new technology at stake, coupled with an understanding of the reasons behind teachers’ choices to adopt or not adopt technology have not yet been fully explored. With the intention of developing a more nuanced understanding of teachers’ technology adoption choices, a conceptual framework using the constructs of teachers’ Professional Dispositions and their Orientation towards Tablet Technology has been derived from the work of Bernstein on the pedagogic discourse, Hoadley and Ensor on Professional Dispositions and Hooper and Rieber on educational technology adoption. Using a mixed methods research methodology, data was collected at three advantaged private secondary schools in which it was found that a relationship does indeed exist between teachers’ Professional Dispositions and their Orientations towards Tablet Technology. From the study it is clear that teachers have principled reasons in relation to their technology adoption, with teachers’ pedagogic mode being critical in shaping decision to adopt or not adopt technology and their construal of their subject knowledge structure influencing the type of technology adoption activities used by teachers, with internet access and productivity being the most widespread and collaboration of learning being the least. Furthermore, it was found that teachers across all Professional Dispositions expect the use of tablets in educational contexts in the future to increase. Keywords: Educational Technology, Tablet Technology, Professional Disposition, Orientation towards Tablet Technology, Pedagogical Discourse, Technology Adoption
A research report submitted to the School of Education, Faculty of Humanities, University of the Witwatersrand in partial fulfilment of the requirements for the degree of Masters of Education Johannesburg March 2014